Validity and Reliability of the Family Satisfaction Scale in University Students of Lima, Peru - Villarreal-Zegarra, David (2017)
The present study is an instrumental research that aims to analyze the psychometric properties of the family satisfaction scale (FSS) in a sample of 607 students from a private university in Lima Metropolitana, aged between 16 and 28 years old. The scale was translated with the inverse method. An exploratory and confirmatory factor analysis was performed, identifying optimal values for a unifactorial solution. The relationship with the family communication variable was analyzed in a positive, direct and moderated effect size. In the analysis of invariance according to sex, it indicated a weak level of invariance. Finally, optimal values of reliability are reported. It is concluded that the FSS presents evidence of validity and reliability, its use being recommended.